The THE ROLE OF ATTRIBUTION THEORY IN EXPLAINING MANAGERIAL AND ACCOUNTING DECISION-MAKING - Qatrinnada, Khansa Nayra; Kesuma, Sambas Ade (Jurnal Riset Terapan Akuntansi, 2026)
This study aims to analyze the role of attribution theory in explaining managerial and accounting decision-making through a Systematic Literature Review (SLR) approach attribution theory proposes that individuals interpret events by assigning them to internal causes, such as ability or intention, or to external causes, such as situational pressure or environmental factors. Using PRISMA guidelines, this study reviewed 21 Scopus-indexed articles published between 2020 and 2025, limited to the Business, Management, and Accounting fields and written in English. The findings show that attribution theory is widely applied to explain how managers evaluate performance outcomes, how stakeholders interpret corporate disclosures, and how consumers assess organizational actions. When organizational decisions are perceived as internally motivated and sincere, they lead to positive outcomes such as increased trust, satisfaction, and reputation. Conversely, decisions perceived as externally driven or manipulative tend to generate skepticism and negative evaluations. This study contributes to the literature by synthesizing recent empirical evidence on the application of attribution theory in managerial and accounting contexts, thereby clarifying its role in shaping evaluative and behavioral decision-making outcomes. Practically, the findings provide insights for managers, accountants, and organizations to improve performance evaluation, communication strategies, and disclosure practices by considering how attribution processes influence stakeholder perceptions. Keywords: : Attribution Theory, Managerial Decision-Making, Accounting Decision- Making, Internal and External Attribution, Organizational Behavior.